Informing Data to Care: Contacting Persons Sampled for the Medical Monitoring Project. (1st September 2019) - Beer, Linda; Bosh, Karin A.; Chowdhury, Pranesh P.; Craw, Jason; Nyaku, Margaret A.; Luna-Gierke, Ruth E.; Sanders, Catherine C.; Shouse, R. Luke
Abstract : Background: Data to care (D2C) is a public health strategy that uses HIV surveillance and other data to identify persons in need of HIV medical care. The Medical Monitoring Project (MMP), which uses similar methods to contact and recruit HIV-positive persons, may inform predictors of successful contact for D2C programs. Setting: MMP is a Centers for Disease Control and Prevention–funded surveillance system that collects nationally representative data on adults with diagnosed HIV in the United States and Puerto Rico. Methods: Using MMP's 2016 data collection cycle, we present contact rates (ie, proportion of HIV-positive persons successfully contacted for MMP) by the age of contact information and age of laboratory test results available from HIV surveillance data. Results: Nationally, 27.6% of eligible persons did not have a recorded laboratory test performed within the past year (project area range: 10.8%–54.6%). The national contact rate among persons with laboratory tests older than 1 year was 37.0% (project area range: 16.5%–67.1%). Higher contact rates were found among persons with more recent laboratory tests. Similar results were found by the age of contact information. Nationally, the most common reason for MMP ineligibility was that the person was deceased; the most common reason for not being contacted was lack of correct contact information. Conclusions: MMP findings suggest that D2C programs would benefit from efforts to improve the quality of HIV surveillance data and local surveillance practices—in particular, death ascertainment, the completeness of laboratory reporting, and the routine updating of contact information. Strengthening collaboration and integration with existing MMP programs may be beneficial.